The Meaning of the Word "Al-Qasiyah" in the Story of Al-Amirah Al-Qasiyah by Kamil Kailani: Paul Ricoeur’s Hermeneutic Perspective - Fajriyah, Nindya Nisfiatul (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This research focuses on analyzing the meaning of the word “al-qasiyah” contained in the story Al-Amirah al-Qasiyah by Kamil Kailani, which relates to issues of bullying, body shaming, and character education that are not only applicable in the past but remain relevant today. The story is presented in simple Modern Standard Arabic (Fusha) with imaginative metaphors. This study employs a descriptive qualitative method with Paul Ricoeur’s Hermeneutic approach, utilizing library research techniques as the source of primary and secondary data. The results indicate that the word “al-qasiyah” (the cruel/the hard-hearted) attributed to the “princes al-Amirah” does not carry a spontaneous meaning, but rather serves as a metaphor for bad attitudes and a destructive ego toward those closest to her, which can only be restored through a significant transformation within the individual. This character change proves that the story is not merely a simple moral reading, but an important contribution to the study of Arabic children’s literature in dissecting “antagonistic” characters as subjects undergoing existential crises. Thus, this research offers a new perspective on understanding the philosophical depth and narrative complexity in classic children’s literature that remains relevant in addressing modern social issues.